Revitalizing Indian Agriculture and Boosting Farmer Incomes - Gulati, Ashok; Roy, Ranjana; Saini, Shweta (India Studies in Business and Economics,, 2021)
This open access book provides an evidence-based roadmap for revitalising Indian agriculture while ensuring that the growth process is efficient, inclusive, and sustainable, and results in sustained growth of farmers' incomes. The book, instead of looking for global best practices and evaluating them to assess the possibility of replicating these domestically, looks inward at the best practices and experiences within Indian states, to answer questions such as -- how the agricultural growth process can be speeded up and made more inclusive, and financially viable; are there any best practices that can be studied and replicated to bring about faster growth in agriculture; does the prior hypothesis that rapid agricultural growth can alleviate poverty faster, reduce malnutrition, and augment farmers' incomes stand? To answer these questions, the book follows four broad threads -- i) Linkage between agricultural performance, poverty and malnutrition; ii) Analysing the historical growth performance of agricultural sector in selected Indian states; iii) Will higher agricultural GDP necessarily result in higher incomes for farmers; iv) Analysing the current agricultural policy environment to evaluate its efficiency and efficacy, and consolidate all analysis to create a roadmap. These are discussed in 12 chapters, which provide a building block for the concluding chapter that presents a roadmap for revitalising Indian agriculture while ensuring growth in farmers' incomes.